IN SILICO COMPARATIVE ANALYSIS OF METABOLIC PATHWAYS OF Heamophilus influenzae AND Helicobacter pylori TO IDENTIFY POTENTIAL DRUG TARGETS - SNEHAL NANDODE; MANOJ DAMALE; SANJAY HARKE (International Journal of Pharma and Bio Sciences, 2012)
Multiple drug resistance of pathogenic bacteria is threat to human health and hence there is an urgent need to identify new drug targets. Due to advances in sequencing techniques complete genomic sequences and metabolic pathways of many bacterias are available. Comparative pathway analysis in pathogenic bacterias and Homo sapiens can lead to identification of new drug targets. In order to identify potential drug targets in Heamophilus influenzae and Helicobacter Pylori in silico metabolic pathways analysis was carried out. Metabolic enzymes of Heamophilus influenzae and Helicobacter Pylori with no homolog in Homo sapiens have been identified at E value 0.01 by BLASTP. Essential enzymes and choke point reactions were identified by using database of essential genes and Choke point reaction finder tool respectively. Metabolic enzyme which are essential to pathogen, show no homolog in Homo sapiens and catalyze choke point reactions have been identified as potential drug targets in current study.